Proses Tindak Pidana Pelaku Kelalaian Laka Lantas Yang Mengakibatkan Orang Lain Meninggal Dunia (Studi Kasus Penegakan Hukum Satlantas Polres Tuban) - Panjaitan, Dahliana Feby Adita (Jurnal Ilmiah Wahana Pendidikan, 2024)
The high rate of traffic accidents is often caused by negligence and lack of understanding from the public. Various factors cause motor vehicle drivers to have accidents, including fatigue, the influence of alcohol and illegal drugs. On the other hand, the condition of the driver's unpreparedness, such as being careless, sleepy, unskilled, tired, not keeping his distance, going too fast opens up great opportunities for accidents to occur. This study seeks to explain how legal provisions and law enforcement criminal cases against perpetrators of negligent accidents that cause other people to die. The approach method used in this study is the case approach which aims to uncover the application of legal norms or rules in legal practice. While the cases that have been decided, as can be seen in the jurisprudence of cases that are the focus of research and statutory approaches (Statute Approach). The results of the study show that in the process of law enforcement traffic accidents are separated into two, namely violations and crimes. This is because to carry out a prosecution before the law, the incident must be a crime. Meanwhile, in traffic accidents, crimes that occur can be categorized as unintentional crimes or caused by acts of negligence or negligence.